Особенности нервных структур некоторых амфибий и млекопитающих - Хворостяная, Т.Т. (Вестник зоологии, 1974)
As a result of studies in 50 amphibians and mammals the conclusion can be made that in the process of phylogenesis the morphological structure of nerve structures is complicated reaching the high level of specialization in mammals. Investigations of the enzymatic activity of the nerve structures by Homori (ACE, acidic phosphatase) indicate the high level of functional activity of nervous elements in mammals as distinct from nervous apparata in amphibians.